BaTiO3: Barium Titanate Nanostructures and Thin Films for Photonics (Advanced Optical Materials 24/2020). Issue 24 (17th December 2020) - Karvounis, Artemios; Timpu, Flavia; Vogler‐Neuling, Viola V.; Savo, Romolo; Grange, Rachel
Abstract : Artemios Karvounis, Rachel Grange and co‐workers review the recent progress of photonic nanostructures and thin films based on barium titanate (see article number 2001249 ). Barium titanate is a noncentrosymmetric crystal utilised in a various spectrum of applications from nonlinear optics and biophotonics up to electro‐optics and photonic waveguides. The significance of this material platform relies on the plethora of growth capabilities either through bottom‐up or top‐down methods. The strong electrooptic response, the intrinsic second‐order nonlinearity, and the tunable optoelectronic properties configure a technological platform of high interest.